Directions to prevent the sexual exploitation of children in tourism: the experience of Ukraine - Доляновська, Інна Миколаївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2013)
The article analyzes the positive and negative aspects of development in Ukraine of such phenomena astourism, which resulted in the ways of preventing violations of the rights of children in tourism, especially during the use of children in sex tourism.